18 Retrospective audit to assess for differences between patients dying of Covid-19 vs patients dying of other causes. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Creed, Jennifer; Tredgett, Kate; Alim, Lina; Gaze, Holly; Qamar, Sombul
Abstract : Background: Specialist palliative care is essential in caring for patients dying of Covid-19. Facing this new disease, it is essential we develop an understanding of this patient population and how best to manage their end of life. We wanted to assess if there are any significant differences between patients dying of Covid-19 versus those dying of other causes. Methods: We compared the patients who died of Covid-19 in April 2020, with patients who died in April 2020 and April 2019 without Covid-19 who were known to the specialist palliative care team at a district general hospital. We collected the data by retrospective case note review. Results: Total of 39 patients; 12 patients in the Covid-positive group, 15 in the Non-Covid-2020 group and 12 in the Non-Covid-2019 group. There were 25 males distributed across the groups, with a comparable median age across the groups. Malignancy was less common in the Covid-positive group but co-morbidities including cardio-vascular disease and type two diabetes were more common. Patients who were Covid-positive; had a shorter window of palliative care team involvement, a lower AKPS at point of referral and were more likely to be in the dying phase of illness. Symptoms of breathlessness were more likely in the Covid-positive group, but they were less likely to have pain. Agitation was present across all groups. The median doses of morphine and midazolam were very similar across all groups and for all groups these treatments were recorded as being effective. Conclusion: The palliative care team were referred patients with Covid-19 at a later stage in their illness. The symptom burden and medication requirements at the end of life were however similar across all groups. It is helpful to be aware of these findings so that we can care for patients dying of Covid-19 effectively.